2017
DOI: 10.3390/w9040282
|View full text |Cite
|
Sign up to set email alerts
|

Large Differences between Glaciers 3D Surface Extents and 2D Planar Areas in Central Tianshan

Abstract: Most glaciers in China lie in high mountainous environments and have relatively large surface slopes. Common analyses consider glaciers' projected areas (2D Area) in a two-dimensional plane, which are much smaller than glacier's topographic surface extents (3D Area). The areal difference between 2D planar areas and 3D surface extents exceeds −5% when the glacier's surface slope is larger than 18 • . In this study, we establish a 3D model in the Muzart Glacier catchment using ASTER GDEM data. This model is used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 26 publications
(44 reference statements)
1
8
0
Order By: Relevance
“…The glacier outlines in this study were corrected by comparing the images acquired in different years, seasons and time, on a 3D surface view for shade verification and on GoogleEearth. The clean ice accuracy (90.8%) against the high resolution GeoEye01 image in 2013 is similar to that reported in the literature, e.g., 89.3% in the Muzart Glacier Catchment [20], 93% for clean ice in the Mount Manaslu in Nepal using object-based classification from Landsat images [35], 95% for clean ice by the band ratio method in European Alps and Chugach Mountains, Alaska [49]. The relatively larger difference (~10%) in this study is mainly attributed to the coarser Landsat image (30 m) against the higher spatial resolution of the GeoEye01 image (4 m), which can detect more small glaciers, glacier edges and terminus than the former.…”
Section: Glacier Mappingsupporting
confidence: 87%
See 2 more Smart Citations
“…The glacier outlines in this study were corrected by comparing the images acquired in different years, seasons and time, on a 3D surface view for shade verification and on GoogleEearth. The clean ice accuracy (90.8%) against the high resolution GeoEye01 image in 2013 is similar to that reported in the literature, e.g., 89.3% in the Muzart Glacier Catchment [20], 93% for clean ice in the Mount Manaslu in Nepal using object-based classification from Landsat images [35], 95% for clean ice by the band ratio method in European Alps and Chugach Mountains, Alaska [49]. The relatively larger difference (~10%) in this study is mainly attributed to the coarser Landsat image (30 m) against the higher spatial resolution of the GeoEye01 image (4 m), which can detect more small glaciers, glacier edges and terminus than the former.…”
Section: Glacier Mappingsupporting
confidence: 87%
“…Although there are large areas of debris-covered glaciers (729 km 2 in 2007) in the Central Tianshan (Southern Inylchek, Tomur, and Koxkar glacier) and their surface thinning is considerable, their areas were relatively stable and only shrank slightly by 1.7 ± 4.8% from 1975 to 2008 [27,31]. Therefore, this study only focuses on clean ice mapping and change analysis from Landsat images using the object-based classification approach, which makes full use of the image reflectance, texture and topographic information and is efficient in manual correction after the initial classification [20].…”
Section: Object-based Image Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Water resources mapping and management Glaciers mapping Landsat, ASTER GDEM, GIS, TIN 3D model. [36] Soil moisture detection GPR, CMP, FO, GIS spatial analysis [16] Groundwater and subsidence analysis GIS spatial analysis, GPS [37] Irrigation planning UAV, HTM for video image classification, GIS visualization [32] Rainfall measurements and design storm…”
Section: Application Fields Specific Contents Gis Algorithm Model mentioning
confidence: 99%
“…In the high Tianshan Mountains, most glaciers lie on steep slopes, and their actual surface extent (3D area) may be much larger than the 2D area. Wang et al [36] in this special issue establish a 3D model to quantify glaciers' 3D and 2D area differences in the Muzart Glacier catchment and in Central Tianshan using ASTER GDEM data, CGI2 and Landsat images. They found that glaciers' 3D areas was 34.2% larger than their 2D areas in the Muzart Glacier catchment and by 27.9% in the entire Central Tianshan, where glaciers' 3D areas reduced by 115 km 2 between 2007 and 2013, being 27.6% larger than their 2D area reduction.…”
Section: Water Resources Mapping and Managementmentioning
confidence: 99%